Model Inovasi Hibah dan Bansos Online Kota Bandung - Nugroho, Candra Setya; Setiawan, Wawan Dharma (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2017)
The management of grants and bansos funds has become a problem in several local governments. The problem of grant and bansos management is related to transparency and accountability. Bandung City Government seeks to improve its public services by innovating the management of grants and bansos through the media website called Sabilulungan or Grants and Bansos Online to solve the problem. Through this research there will be discussed related to the management model of grants and bansos through grants and online bansos. This research uses descriptive qualitative research method (more specifically with the method of